2004
DOI: 10.1152/ajpgi.00498.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activation of β-catenin signaling in human epithelia

Abstract: The mucosal lining of the human intestine is constantly bathed in a milieu of commensal gut flora, the vast majority of these being nonpathogenic microorganisms. Here, we demonstrate that microbial-epithelial cell interactions not only affect proinflammatory pathways but also influence beta-catenin signaling, a key component in regulating epithelial cell proliferation. The nonpathogenic Salmonella strain PhoP(c) activates the beta-catenin signaling pathway of human epithelia via a blockade of beta-catenin degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 28 publications
5
108
1
1
Order By: Relevance
“…5 Additionally, we showed that AvrA inhibited the NF-kB pathways and consequently modulated cellular inflammation. 27 We believe that the bacterial effector AvrA regulates the activation of NF-kB through b-catenin stabilization.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 Additionally, we showed that AvrA inhibited the NF-kB pathways and consequently modulated cellular inflammation. 27 We believe that the bacterial effector AvrA regulates the activation of NF-kB through b-catenin stabilization.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, non-pathogenic bacteria stabilize b-catenin by inhibiting b-catenin phosphorylation through GSK-3b and ubiquitination of b-catenin. 5 Stabilization of b-catenin represses NF-kB-dependent inflammatory pathways and inhibits IL-8 secretion during bacterial colonization (Figure 7b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the YopJ-like molecule from Salmonella typhimurium, AvrA, has been reported to inhibit the NF-B pathway (22) and also to inhibit the degradation of ␤-catenin (23). Phosphorylation of ␤-catenin occurs within a motif that is highly similar to the phosphorylation motif of I B (14) and it has been suggested that IKK␣ may phosphorylate and regulate the deg- radation of ␤-catenin (24).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella typhimurium wild-type strain (WT-SL) and nonpathogenic strain PhoP c (28) were used in this study. Nonagitated microaerophilic bacterial cultures were prepared by inoculating 10 ml of Luria-Bertani broth with 0.01 ml of a stationary phase culture followed by overnight incubation (ϳ18 h) at 37°C, as previously described (38).…”
Section: Methodsmentioning
confidence: 99%